Effects of Flyash and Plant Hormones Treated Soil on the Increased Protein and Amino Acid Contents in the Seeds of Ground Nut (Arachis hypogaea) - SAO, SHWETA; GOTHALWAL, RAGINI; THETWAR, L.K.; DESHMUKH, N.C.; KUMAR JANGDE, ASHOK; KESHKAR, GIRISH (Asian Journal of Chemistry, 2010)
Soils of newly formed Chhattisgarh state are acidic (red, yellow) and soil acidity is responsible for Al3+ ion toxicity which leads to reduced micro organism activity, as well as Mo and Zn deficiency. In plants indole acetic acid and giberellic acid were used as growth hormones. Plant growth parameters were compared for plain and flyash and hormone treated soil.